Peranan Psychological Capital Karyawan Dalam Mendorong Ekspektasi Kinerja Perusahaan - Sari, Yunita; Yunianto, Andika (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
The world’s economic growth has made competition in the business world even tighter, so companies must have good achievements to get success in the business world. This is the biggest challenge for organizations to survive and adapt to any changes that occur. For that the company must be able to increase the ability and potential of employees. Efforts to improve the quality and effectiveness of employees need serious attention by the company by referring to the development of information technology and the readiness of human resources. The work effectiveness of company employees is not only determined by the rules and Standard Operational Procedure (SOP). Employees with a high level of performance expectations show a positive attitude towards their work, on the other hand someone who does not have performance expectations with their work shows a negative attitude towards work. Therefore, the company is expected to generate psychological capital that can boost employee performance expectations, where psychological capital reflects a positive psychological condition. By measuring the success of the application of the psychological capital role of employees in encouraging expectations of company performance, it is able to generate employee confidence in solving problems and success at work